Significance of Serum Soluble Fas (sFas/CD95) and Tumor Necrosis Factor- Alpha (TNF-α) in Radiologically Diagnosed Patients with Uterine Leiomyoma - Hayfaa Salman Al Hadithi; Nadia Hameed Mohammed2 (College of Pharmacy / Mustansiriyah University, 2018)
Leiomyoma is a common benign tumor of female reproductive system arising from the smooth muscle cells of uterus. About 17.8% of females in 40s age group and 77% of hysterectomies found to have leiomyoma. It affects females in reproductive age and cause pelvic pain, abortion, infertility, menorrhagia which in some cases ends by hysterectomy. In this study the extrinsic apoptotic pathway was evaluated in patients with uterine leiomyoma by measuring serum soluble Fas (sFas) and Tumor Necrosis Factor Alpha (TNFα) in both patients and control healthy women. Forty patients with leiomyoma from 22-52 years old were involved in this study. Forty apparently healthy, their ages matched volunteers were selected as a control. Four ml of venous blood sample was obtained from each, serum was separated and serum concentration of sFas and TNFα measured using ELISA technique. There was a highly significant increase in serum concentration of TNF-α in patients with leiomyoma (mean 0.579pg/ml ± SE 0.039) than control group (mean 0.120pg/ml ± SE 0.007), also there was a highly significant increase in serum concentration of sFas of patient (mean 0.326pg/ml ± SE 0.028) compared to control healthy subjects (mean 0.126pg/ml ± 0.025). Receiver Operator Characteristic (ROC) curve for determination of TNFα and sFas cutoff value shows that TNFα has cutoff value of ≥0.220pg/ml with 97.5% sensitivity and 100% specificity for leiomyoma and accuracy rate of 99.6%. The sFas cutoff value is ≥0.154pg/ml with 80% sensitivity and 82.5% specificity for leiomyoma and accuracy rate of 87.4%.